2016
DOI: 10.1038/ncomms13579
|View full text |Cite
|
Sign up to set email alerts
|

Tectal-derived interneurons contribute to phasic and tonic inhibition in the visual thalamus

Abstract: The release of GABA from local interneurons in the dorsal lateral geniculate nucleus (dLGN-INs) provides inhibitory control during visual processing within the thalamus. It is commonly assumed that this important class of interneurons originates from within the thalamic complex, but we now show that during early postnatal development Sox14/Otx2-expressing precursor cells migrate from the dorsal midbrain to generate dLGN-INs. The unexpected extra-diencephalic origin of dLGN-INs sets them apart from GABAergic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(105 citation statements)
references
References 67 publications
8
95
2
Order By: Relevance
“…The arrival of these interneurons occurs postnatally, after retinal inputs have targeted dLGN, formed immature connections, and begun to undergo activity-dependent refinement (Jones & Rubenstein, 2004; Singh et al, 2012; Golding et al, 2014; Jager et al, 2016). The precise origin of these interneurons is currently under debate, with studies suggesting they arise from a rostral progenitor domain within the thalamus (i.e., prosomer 3) or from tectum (Virolainen et al, 2012; Golding et al, 2014; Jager et al, 2016). Evidence is also emerging that dLGN interneurons are not a homogeneous population in mice, and can instead be divided into at least two classes based on soma size, membrane capacitance, and neuronal nitric oxide synthase (nNOS) expression (Leist et al, 2016).…”
Section: Cytoarchitectural Organization Of Retinorecipient Thalamic Nmentioning
confidence: 99%
“…The arrival of these interneurons occurs postnatally, after retinal inputs have targeted dLGN, formed immature connections, and begun to undergo activity-dependent refinement (Jones & Rubenstein, 2004; Singh et al, 2012; Golding et al, 2014; Jager et al, 2016). The precise origin of these interneurons is currently under debate, with studies suggesting they arise from a rostral progenitor domain within the thalamus (i.e., prosomer 3) or from tectum (Virolainen et al, 2012; Golding et al, 2014; Jager et al, 2016). Evidence is also emerging that dLGN interneurons are not a homogeneous population in mice, and can instead be divided into at least two classes based on soma size, membrane capacitance, and neuronal nitric oxide synthase (nNOS) expression (Leist et al, 2016).…”
Section: Cytoarchitectural Organization Of Retinorecipient Thalamic Nmentioning
confidence: 99%
“…How could these differences arise as part of species-specific ontogenesis of thalamic interneurons? We have previously shown that in the mouse, interneurons in the FO visual thalamus, the dorsal lateral geniculate nucleus (dLGN), originate in the midbrain from an En1 + Gata2 + Otx2 + Sox14 + lineage (Jager et al, 2016). On the other hand, earlier work in humans has suggested the Dlx1/2 -expressing ganglionic eminences (GE) in the telencephalon as the source of interneurons for the HO thalamic nuclei-the mediodorsal nucleus and the pulvinar (Rakić and Sidman, 1969; Letinić and Kostović, 1997; Letinic and Rakic, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, spillover of GABA onto these δ subunit-containing extrasynaptic GABA A Rs occurs onto VB relay neurons in response to stimulated burst firing of the nRT (Herd et al, 2013). Similarly, we recently reported that DS-2 application resulted in a slowing of ChR2-evoked IPSCs that are driven by optogenetic GABA release from dLGN interneurons (Jager et al, 2016). These results are not contradictory if the magnitude of the GABA transient associated with spontaneous release were much less than the GABA transient associated with evoked release.…”
Section: Discussionmentioning
confidence: 55%